Optimizing Acute Pyelonephritis Diagnosis through Doppler Ultrasound Imaging (Eurasian Medical Research Periodical, 2025)
This article describes the way of improving the diagnosis of cute pyelonephritis, which is a bacterial infection of the renal pelvis and parenchyma most commonly seen in young women. It remains common and continues to have significant morbidity in certain groups of patients, using doppleroghraphy.